Implementasi Kebijakan Peraturan Menteri Dalam NegeriRepublik Indonesia Nomor 19 Tahun 2018 Tentang Peningkatan Kualitas Layanan Administrasi Kependudukan - Biringan, Roni; Mesangi, Evie; Pangkey, Itje (Academy of Education Journal, 2024)
This study is motivated by the suboptimal quality of population administration services in Bitung City. The aim of this research is to examine the implementation of the Ministry of Home Affairs Regulation Number 19 of 2018 on Improving the Quality of Population Administration Services in Bitung City and the factors influencing it. This research employs a qualitative descriptive method. Data sources were obtained through observation, interviews, and documentation. The data analysis techniques used include data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the Ministry of Home Affairs Regulation Number 19 of 2018 on improving population administration services in Bitung City has been carried out but has not been effective and optimal. Factors influencing the quality of population administration services in Bitung City include inter-departmental coordination, supporting infrastructure, and budget availability.